Cloud Computing and Firm Growth - Timothy DeStefano; Richard Kneller; Jonathan Timmis (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Cloud computing enables a shift in the costs of ICT adoption from investment in fixed capital to pay-on-demand services allowing firms to scale and reorganize. Using new firm-level data we examine the impact of cloud on firm growth, using zip-code-level instruments of the timing of high-speed fiber availability and speeds. Cloud leads to the growth of employment and revenue for young firms, but they become concentrated in fewer establishments. For incumbents, we find smaller scale effects but dispersed activity through closing establishments and moving employment farther from the headquarters. Moreover, cloud adoption leads to worker relocation across establishments within firms.
Keywords: J23; J24; L20; O33; 330; cloud; digital; productivity; firms